Bank Garansi: Implementasi Pada Perbankan Syariah Di PT. Bank Muamalat Kantor Cabang Medan Balaikota - Rahmayati Rahmayati (AGHNIYA : Jurnal Ekonomi Islam, 2021)
This study aims to analyze how the provision of bank guarantees and the implementation of bank guarantees in banking which are implemented by PT. Bank Muamalat Medan Branch Office City Hall. The problems that will be discussed are how to implement a bank guarantee in the case study of PT. Bank Muamalat Medan Branch Office City Hall. This research method uses a qualitative method that is using a case study approach in the form of theory, interviews, documentation at PT. Bank Muamalat Medan Branch Office City Hall. The results obtained are that the implementation of bank guarantees has followed the terms and conditions in the form of guarantees in a project where the bank guarantee opening system through the work that must be done by the parties involved in the bank guarantee consisting of contractors, employers, and banks have done a way that regularly linked together to facilitate the flow of information within the bank guarantee. Where is the guarantee provided by the bank for the benefit of the customer who guarantees the recipient of the guarantee (third party) if the customer defaults (does not fulfill the obligation) to the guarantor (third party) according to the agreed time.